ISOLASI BAKTERI PENGHASIL ENZIM PROTEASE STAPHYLOCOCCUS HOMINIS PADA ONCOM MERAH PASCA FERMENTASI 120 JAM - Aulia Harun; Sakti Imam Muchlissin; Ana Hidayati Mukaromah; Sri Darmawati; Stalis Norma Ethica (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Enzymes are complex protein moleculer produced by living cells playing role as catalysts in various chemical processes in the body. Among enzymes playing an important role in human life is protease. The purpose of this study was to determine the presence of protease – producing bacteria found on 120-h post - fermented oncom and to identify the bacteria based on its 16S   rRNA gene analysis. Bacterial isolation and purification was carried out using Nutrient Agar media with spread technique. Of the six bacterial isolates isolated from the oncom sample after 120 hours of fermentation, there was one isolate that had protease activity, namely IROD 5. The protease enzyme income test was carried out using Skim Milk Agar media. Molecular identification process was carried out through sequential analysis of 16S rRNA using PCR method using primers forward F: 5'-AGAGTTGATCCTGGCTCAG-3 'and reverse R: 5'- GGTTACCTTGTTAC. GACTT-3 primers' followed by sequencing process. The protease enzyme production test to bacterial isolate was conducted using Skim Milk Agar. Molecular identification was performed through analysis of 16S rRNA gene sequence using PCR method followed by sequencing process. A single bacterial isolate having proteolytic activity was obtained based on observation of the clear zone of protease surrounding the bacterial colony with a diameter of 72 mm. The 16S rRNA gene sequence of the obtained proteolytic bacterial strain IROD5 has been obtained and analysis on the gene sequence resulted 99% similarity levels with sequence of similar gene s of Staphylococcus hominis. As conclusion, the obtained bacterial isolate in this studyis apotential protease  enzyme  producer  and  molecularly  identified  as  Staphylococcus hominis strains IROD5. Keyword : Protease Enzyme, Gen 16S rRNA, Red Oncom